2020
DOI: 10.1126/sciadv.aay5178
|View full text |Cite
|
Sign up to set email alerts
|

Quartz, mica, and amphibole exsolution from majoritic garnet reveals ultra-deep sediment subduction, Appalachian orogen

Abstract: Diamond and coesite are classic indicators of ultrahigh-pressure (UHP; ≥100-kilometer depth) metamorphism, but they readily recrystallize during exhumation. Crystallographically oriented pyroxene and amphibole exsolution lamellae in garnet document decomposed supersilicic UHP majoritic garnet originally stable at diamond-grade conditions, but majoritic precursors have only been quantitatively demonstrated in mafic and ultramafic rocks. Moreover, controversy persists regarding which silicates majoritic garnet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…380 Ma (Gatewood et al., 2015; Vance & Holland, 1993). Within the Northern Appalachians, localized bodies were metamorphosed at UH T conditions (Ague & Eckert, 2012; Ague et al., 2013; Keller and Ague, 2020); evidence of UHP metamorphism also has been proposed (Keller and Ague, 2020; Peterman, Snoeyenbos, et al., 2016; Snoeyenbos et al, 2011), but neither coesite nor diamond have been reported in the Northern Appalachians. Samples of metapelites from the Northern Appalachians, USA, were collected from the Cobble Mountain Formation, the Gassetts Schist, the Straits Schist, and the Slashers Ledges Formation.…”
Section: Geologic Background Of the Samplesmentioning
confidence: 99%
“…380 Ma (Gatewood et al., 2015; Vance & Holland, 1993). Within the Northern Appalachians, localized bodies were metamorphosed at UH T conditions (Ague & Eckert, 2012; Ague et al., 2013; Keller and Ague, 2020); evidence of UHP metamorphism also has been proposed (Keller and Ague, 2020; Peterman, Snoeyenbos, et al., 2016; Snoeyenbos et al, 2011), but neither coesite nor diamond have been reported in the Northern Appalachians. Samples of metapelites from the Northern Appalachians, USA, were collected from the Cobble Mountain Formation, the Gassetts Schist, the Straits Schist, and the Slashers Ledges Formation.…”
Section: Geologic Background Of the Samplesmentioning
confidence: 99%
“…Miocene in age, have been also recently reported (Pownall et al, 2018). More recent studies of other rocks in the CMT document high-pressure granulite facies metamorphism (~1050 °C, ~1.8 GPa) of silicaundersaturated garnet-spinel-corundum gneisses (Keller and Ague, 2018), as well as UHP metamorphism (Keller and Ague, 2020).…”
Section: Introductionmentioning
confidence: 97%
“… Proposed pressure-temperature (PT) conditions of the UHP garnet from the Running River Metamorphics. Exsolution mineralogy fields from ( 4 ). Minimum peak P-T conditions (blue triangle) of 3.5 to 4 GPa at 800° to 900°C are constrained by metamorphic diamond inclusions and Zr in rutile thermometry.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of ultrahigh pressure (UHP) metamorphism is important for the tectonic reconstruction of ancient terranes. UHP metamorphism is typically interpreted to indicate collisional orogenesis and deep subduction (>70 km) of continental material (1)(2)(3)(4). Continental material may be subducted to depths >200 km (5-7) before exhumation and emplacement along continental suture zones.…”
Section: Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation